Numerical Investigation of β-Amyloid Aggregation Process In Alzheimer’s Disease - Wibowo Zefanya Putri Rida; Budiasih Lusia Krismiyati (ITM Web of Conferences)
The process of β-amyloid (Aβ) protein aggregation in Alzheimer’s disease can be represented by a mathematical model. The model is built based on several groups representing the concentrations of a number of monomer and the concentration of oligomer, which is presented as a system of nonlinear ordinary differential equations. In this paper, the extinction and interior equilibrium point are also determined. The model will be solved numerically by the fourth-order Runge-Kutta method and it is shown that the solution will lead to the equilibrium point obtained. Some numerical investigations are done by analyzing the effect of monomer number that occur. It can be concluded that the greater the number of monomers considered, the lower the concentration of oligomers, so that it can reduce the symptoms of Alzheimer’s disease. Moreover, for the greater capacity of the Aβ protein, the faster monomers aggregation process occurs.